2001
DOI: 10.3354/dao047183
|View full text |Cite
|
Sign up to set email alerts
|

Disposition of 14C-flumequine in eel Anguilla anguilla, turbot Scophthalmus maximus and halibut Hippoglossus hippoglossus after oral and intravenous administration

Abstract: The absorption, distribution and elimination of 14 C-labelled flumequine were studied using whole body autoradiography and liquid scintillation counting. Flumequine was administered to eel Anguilla anguilla, turbot Scophthalmus maximus and halibut Hippoglossus hippoglossus intravenously and orally as a single dose of 5 mg kg . The turbot and halibut studies were performed in salt water (salinity of 32 ‰) at temperatures of 16 ± 1°C (turbot) and 9.5 ± 0.5°C (halibut). The eel study was conducted in fresh water … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 43 publications
(34 reference statements)
0
9
0
Order By: Relevance
“…These authors suggested that physiological and anatomical differences of eel gills may be responsible for this difference. The gills are regarded as an important sites of elimination of xenobiotics in fish (Hansen et al 2001); however, the gills and the circulation system of eels are characterized by an extremely low gill surface area, low blood hematocrit, small ventricular masses, and relatively low cardiac output, which results in the gills being less perfused than in other fish (Byczkowska-Smyk 1958, Hansen & Horsberg 2000. In mammals, t 1/2β values are significantly shorter than in fish.…”
Section: Discussionmentioning
confidence: 99%
“…These authors suggested that physiological and anatomical differences of eel gills may be responsible for this difference. The gills are regarded as an important sites of elimination of xenobiotics in fish (Hansen et al 2001); however, the gills and the circulation system of eels are characterized by an extremely low gill surface area, low blood hematocrit, small ventricular masses, and relatively low cardiac output, which results in the gills being less perfused than in other fish (Byczkowska-Smyk 1958, Hansen & Horsberg 2000. In mammals, t 1/2β values are significantly shorter than in fish.…”
Section: Discussionmentioning
confidence: 99%
“…Gill was regarded as one of the most important elimination organs of xenobiotics in fish, due to the large surface area and blood flow together with the short distance between the blood and water (Hansen et al 2001). It was concluded that florfenicol and its metabolite in seawater tilapia may be mainly excreted by gill (Feng et al 2008).…”
mentioning
confidence: 99%
“…Meanwhile, the Japanese eels (Anguilla japonica) spawning ground appears to be in the west of the Mariana Islands in the North Pacific (Katoh & Kobayashi 2001;Tsukamoto & Arai 2001;Ringuet et al 2002;Tseng et al 2003;Tsukamoto 2006). Species of the Anguillidae family, especially the A. anguilla (Virbickas 2000;Hansen et al 2001;Tzchori et al 2004), the American eel and the Japanese eel (Katoh & Kobayashi 2001) are of great commercial interest (Jing & Li 1999;Tsukamoto & Arai 2001;Ringuet et al 2002;Altun et al 2005). Consequently, a decrease in European (Limburg et al 2003;Dannewitz et al 2005), American (Wirth & Bernatchez 2003) and Japanese eel (Tseng et al 2003) catches during the past decades in Europe, America and Asia, respectively, has inspired many studies on physiological (Ellerby et al 2001a, b), ecological (Poole & Reynolds 1998;Tzeng et al 1999;Okamura et al 2002;Bardonnet & Riera 2005;Palstra et al 2006) and genetic (Jing & Li 1999;Wirth & Bernatchez 2001Mank & Avise 2003;Tseng et al 2003;Dannewitz et al 2005) aspects of eel biology and an increased concern over the eel restocking strategy (Ringuet et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, Lithuanian fishery in the coastal waters and the Curonian Lagoon depends on natural recruitment primarily, while restocking is still not very essential. Furthermore, besides other eel restocking problems, such as spread of parasites or infections (Madsen et al 2000;Hansen et al 2001;Marco-Noales et al 2001;Kirk et al 2002;Shin 2004), eel restocking can modify genetic variability and even reduce reproductive success if genetic differentiation in A. anguilla populations exists. This study presents results of the initial investigation into the A. anguilla population in Lithuania using microsatellite DNA markers.…”
Section: Introductionmentioning
confidence: 99%